Politik Hukum terhadap Hak Ulayat dalam Simpul Landreform (Reformasi Lahan) di Indonesia - Gustiva Andri (Jurnal Hukum Lex Generalis, 2024)
This article discusses the legal politics of customary rights in land reform in Indonesia, as well as the concept of reform. Through the legal norms approach, several problems were found in managing agrarian affairs, including: inequality in state land control, overlapping land distribution policies in the past, the emergence of social and ecological crises in rural areas and the non-functioning of UUPA. So to overcome this problem, the Government needs to take strategic steps to reform the existing agrarian law. Pancasila and the constitution must be the spirit and soul of national agrarian law reform. So that existing land and agrarian resources will no longer be used as trading material.